Quercetin modulates Na(+)/K(+) ATPase and sodium hydrogen exchanger in type 2 diabetic erythrocytes - Mishra, N.; Rizvi, S. I. (Cellular and Molecular Biology, 2012)
Quercetin has been reported to possess many important biological properties. We undertook in vitro studies to examine the effect of quercetin on erythrocyte Na+/K+ ATPase and sodium hydrogen exchanger (NHE) activity in normal and type 2 diabetic subjects. A significant (p<0.02) increase in the activities of Na+/K+ ATPase and a decrease (p< 0.01) in NHE were observed in type 2 diabetic subjects compared to normal. In vitro treatment with quercetin caused inhibition of both Na+/K + ATPase and NHE. The inhibitory effect of quercetin was concentration dependent. The effect of quercetin on Na+/K+ ATPase and NHE may be explained due to a direct effect of this compound on plasma membrane leading to a change in membrane fluidity. The data obtained in this study may help to explain the anti-diabetic and anti-carcinogenic role of quercetin.